Poverty and Human Development Report 2011 - Mkukuta Secretariat (Dar es Salaam REPOA, 2012)
PHDR 2011 is the sixth report in the series since 2002. Building upon the foundation of the series to date and growing store of domestic research, this year's report provides an expanded analysis of the trends and outcomes in national development as well as discussion of important socio-economic issues facing the country. Chapter 1 reviews progress towards key development targets based on the national indicators set for Mkukuta's three major clusters of desired outcomes: growth and reduction of income poverty (Cluster I); improvement of quality of life and social well-being (ClusterII); and governance and accountability (Cluster III). In particular, this year's report benefits from the new and expanded data set collected by the 2010 Tanzania Demographic and Health Survey, ground-breaking national studies, such as the 2009 violence against children report, and strengthened by government systems of routine data management and reporting. Chapter 2 and 3 of the report explore the interplay between economic growth,productive employment and poverty reduction to identify policy options that can make future growth in Tanzania more inclusive and pro-poor
Keywords: Poverty reduction, Growth Governance Accountability